Landscape Pattern Changes and Ecological Vulnerability Assessment in Mountainous Regions: A Multi-Scale Analysis of Heishui County, Southwest China - Weiqi Gu; Hong Fu; Wen Jin (Land)
Against the backdrop of intensifying global climate change, the impact of land use pattern changes on ecosystem vulnerability has garnered increasing attention. However, systematic studies concerning the ecological vulnerability of mountainous regions remains inadequate, with relevant policies primarily remaining at the macro-regulation level and lacking specific guidance measures. Taking Heishui County in southwest China as a case study, this research innovatively combines landscape pattern with the sensitivity–pressure–resilience (SPR) model to systematically analyze land use spatiotemporal evolution characteristics, ecological vulnerability and spatial differentiation patterns, and their driving mechanisms across multiple scales, including county, township, and land use types. The findings reveal that the region’s ecological vulnerability exhibits a spatial distribution pattern of “high in the southeast and low in the northwest”, with a radiating decrease from the centers of Longba and Weigu towns. The high degree of farmland landscape fragmentation is identified as a crucial factor contributing to its heightened ecological vulnerability. Geological disasters, human activities, meteorological conditions, and topographical features are the primary driving factors affecting ecological vulnerability intensity. Furthermore, land use pattern changes, characterized by landscape patch fragmentation, lack of dominant patch types, and decreased landscape diversity have further intensified regional ecological vulnerability. This research holds significant theoretical and practical implications for guiding ecological environmental governance in mountainous regions, enhancing ecological resilience, and promoting regional sustainable development.